Enhancing Fishery Product Processing Capacity of Poklahsar Group in Padak Guar Village - Muslihuddin Aini; Pawana Zia Zannititah; Huurul’in Ruhma Ruksalana (DEVOTIONIS, 2026)
This community service activity was conducted to enhance the capacity of the Fish Processing and Marketing Group (Poklahsar) Amertha Bahari in Padak Guar Village, Sambelia District, East Lombok Regency. Coastal communities often face challenges in optimizing the economic value of fishery resources due to limited processing skills, insufficient understanding of food safety standards, and weak capacity in basic business management. These conditions result in low value-added fishery products and limited income opportunities. Therefore, this program aimed to improve participants’ knowledge and skills in fishery product processing, food safety practices, product diversification, and cost of production calculation. The activity was implemented using a participatory training approach that combined theoretical explanations and practical sessions. The program was carried out in one day and included stages of preparation, material delivery, hands-on practice, and evaluation. Training materials covered food safety standards, hygienic handling of fishery products, processing techniques for fish-based products such as fish crackers and fish balls, and calculation of cost of production (HPP) as a basis for determining appropriate selling prices. Evaluation was conducted through observation of participant engagement, assessment of skill mastery during practical sessions, and interactive discussions. The results showed an improvement in participants’ understanding of food safety principles, processing procedures, and basic cost calculations. Participants were able to independently practice the production of fish crackers and fish balls and demonstrated readiness to diversify products into other fish-based processed foods. Overall, this activity contributed positively to strengthening community capacity, increasing the value addition of fishery products, and supporting sustainable livelihoods. Continued mentoring and institutional support are recommended to ensure the long-term sustainability of similar community service programs.